Leche materna como factor protector para el desarrollo de enterocolitis necrosante en neonatos prematuros de bajo peso al nacer - Morales Leiva, Clayderman Pedro Manuel (2014)
To determine whether breastfeeding is protective for necrotizing enterocolitis in preterm low birth weight of the Bethlehem Hospital between 2007-2012 Trujillo factor. Material and Methods: A study of analytical , observational, retrospective, case-control guy who analyzed data from a series of 168 medical records of patients preterm infants with low birth weight were grouped into was carried out : a ) Cases (n = 42 ) preterm infants with low birth weight and diagnosis of necrotizing enterocolitis b ) Controls ( n = 126): premature newborns with low birth weight and without a diagnosis of necrotizing enterocolitis. Results: Of the 168 patients, 137 ( 81.5 %) were breastfeeding and 31 ( 18.5 %) with artificial milk. Comparing both results found that 25 of those who received breast milk developed necrotizing enterocolitis against 112 of them did not develop this disease , and this difference (60 % vs 89%) statistically significant p < 0.05 with an OR 0 , 18 and confidence intervals at 95% from 0.08 to 0.42 . Conclusions: breastfeeding is a protective factor for necrotizing enterocolitis in preterm low birth weight